2015
DOI: 10.1186/s12958-015-0066-4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro decidualisation of canine uterine stromal cells

Abstract: BackgroundThe uterine response to the presence of embryos is poorly understood in the domestic dog (Canis familiaris). The intimate embryo-maternal cross-talk, which begins following the hatching of blastocysts and embryo attachment leads to strong structural and functional remodelling of the uterus. A part of this process is decidualisation, comprising morphological and biochemical changes that result in formation of maternal stroma-derived decidual cells. These are an integral part of the canine placenta mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
73
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(78 citation statements)
references
References 53 publications
5
73
0
Order By: Relevance
“…Consequently, there is emerging evidence identifying PGE2 as an important factor involved in canine decidualization. This assumption is further strengthened by our recent observations from studies investigating the capability of canine uterine stromal cells to undergo decidualization in vitro (Kautz et al., ). Utilizing the cAMP‐mediated approach with stromal cells isolated from naturally oestrogen‐primed uteri from early dioestrus dogs, PTGES was strongly induced during the course of in vitro decidualization (Kautz et al., ).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Consequently, there is emerging evidence identifying PGE2 as an important factor involved in canine decidualization. This assumption is further strengthened by our recent observations from studies investigating the capability of canine uterine stromal cells to undergo decidualization in vitro (Kautz et al., ). Utilizing the cAMP‐mediated approach with stromal cells isolated from naturally oestrogen‐primed uteri from early dioestrus dogs, PTGES was strongly induced during the course of in vitro decidualization (Kautz et al., ).…”
Section: Introductionmentioning
confidence: 70%
“…This assumption is further strengthened by our recent observations from studies investigating the capability of canine uterine stromal cells to undergo decidualization in vitro (Kautz et al., ). Utilizing the cAMP‐mediated approach with stromal cells isolated from naturally oestrogen‐primed uteri from early dioestrus dogs, PTGES was strongly induced during the course of in vitro decidualization (Kautz et al., ). The cAMP‐based protocol was chosen for that study due to its strong decidualization potential as shown previously (Brar et al., ; Gellersen & Brosens, ; Tamura et al., ).…”
Section: Introductionmentioning
confidence: 70%
“…Endometrial receptivity has become one of the research hotspots in recent years, and accumulated evidence suggests that hormones (Young 2013), osteopontin (OPN) (Talbi et al 2006), vascular endothelial growth factor (VEGF) (Lai et al 2015), leukaemia-inhibitory factor (LIF) (Miravet-Valenciano et al 2015), prolactin (PRL) (Kautz et al 2015) and other factors participate in the preparation of endometrial receptivity. In addition, intensive research work has been performed to better understand the regulation of the endometrium and its clinical implications to improve implantation in human, and many genes have been reported to influence endometrial development (Strowitzki et al 2006).…”
Section: Doi: 1017221/15/2017-cjasmentioning
confidence: 99%
“…Specifically, the endometrial stromal cells (ESC) undergo a marked rearrangement of the intracellular architecture and begin to accumulate glycogen, initiating the secretion of various proteins, growth factors, and cytokines, such as PRL, which are induced in ESC during decidualization and are therefore recognized as a marker of decidualization (Gellersen and Brosens 2003). In contrast to human and rodent models, however, canine decidualized cells exhibited very low expression of PRL (Kautz et al 2015). PRL-protein was mainly expressed in the cytoplasm of LE and GE, and in a small amount in SC in dairy goats, notably, there was no difference in LE and GE, but a remarkable increase was found in SC on D15 compared to D5.…”
Section: Doi: 1017221/15/2017-cjasmentioning
confidence: 99%
“…Canine placentation is more invasive than that of the cat, despite their similarities. Absent or scarce decidual vimentin‐positive cells, well described in cat but unsteadily identified in the dog, might partially explain its higher invasiveness (Barbeito, Fernández, Gimeno, & Portiansky, ; Fernández, Barbeito, Portiansky, & Gimeno, ; Fernández et al., ; Kautz et al., ; Walter & Schönkypl, ). Furthermore, several cellular and matrix components participate in the invasive function of the early canine placenta.…”
Section: Introductionmentioning
confidence: 99%